Cultural symbolism and architectural identity: The Bund Finance Center’s role in shaping Shanghai’s urban legacy and contemporary cultural landscape - Khin Thiri Kyaw (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The Bund Finance Center (BFC) in Shanghai exemplifies how contemporary architecture can convey cultural depth while advancing modern urban identity. Designed by Heatherwick Studio and Foster + Partners, the BFC blends kinetic form, traditional materials, and symbolic spatial arrangements to reflect both Shanghai’s heritage and its global aspirations. This study investigates the role of BFC in shaping Shanghai’s architectural identity and cultural narrative by analyzing its spatial symbolism, public perception, and branding influence. Methods: Using a qualitative case study approach, the research draws on visual analysis, design documents, expert literature, and thematic coding of public and professional survey responses. Key features such as the rotating bronze façade, courtyard-like ground plane, and use of stone were widely interpreted as modern expressions of Chinese cultural forms. These design choices position the BFC as both a landmark of innovation and a medium for cultural storytelling. Findings: The findings show that the BFC elicits strong emotional responses; particularly pride and belonging and contributes significantly to Shanghai’s urban branding and civic identity. Its hybrid design reflects a broader movement in urban architecture that seeks to balance tradition with global design narratives. Ultimately, this study demonstrates that the BFC is not only a functional urban space, but also a symbolic bridge between Shanghai’s historical memory and its contemporary ambition. It offers a replicable framework for evaluating culturally embedded design in global cities. Conclusion: This study concludes that the Bund Finance Center functions as an authentic city-branding instrument by reinterpreting cultural heritage through innovative architecture that evokes emotional engagement, reinforces place identity, and strengthens Shanghai’s global urban reputation. Novelty/Originality of this article: This article offers originality by presenting an interdisciplinary framework that positions culturally embedded contemporary architecture as a strategic instrument of city branding, demonstrating how the Bund Finance Center translates architectural symbolism into urban authenticity, emotional attachment, and global brand identity in a competitive city branding context.